Chemical composition of Philippine molasses - Migo, V.P (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1995)
Molasses samples from nine sugar mills in different regions in the Philippines representing and Mindanao were characterized. The samples were analyzed for proximate, sugars, fatty acids, total organic carbon, anions (chloride, fluoride and sulfate) and mineral composition (Na, K, Ca, Mg, P, Fe, Cu, Zn, and Mn). Moisture ranges from 17 to 23%; ash, 6 to 10%; ether extract, 0.34 to 0.85%; and crude protein, 2 to 4%. Total sugars range from 59-69% and are predominantly sucrose, glucose and fructose. Linoleic acid was found to be the most predominant fatty acid; lauric, myristic and palmitoleic acids were found the least in molasses. Total organic carbon ranges from 30 to 38%